(untitled) (TAJ: Journal of Teachers Association, 2019)
Introduction: Febrile convulsion is the most common seizure disorder in the pediatric age group. It occurs in 2-5% of children. A febrile seizure is a seizure accompanied by fever (temperature 100.4°F or 38°C by any method), without central nervous system infection, that occurs in infants and children 6 through 60 months of age. Aim: The study was conducted to see the effect of serum sodium level on the recurrence of febrile seizure during the same febrile illness. Materials and Method: A cross-sectional descriptive study which enrolled 65 children admitted with febrile seizures at 100 bed district hospital, Naogaon. They were divided in to two groups, those with a single seizure and the rest were children with more than one seizures. Serum sodium levels were estimated after stabilization of patients. The probability of recurrent febrile seizures and serum sodium level was analyzed. Results: Hyponatremia (serum sodium <135 mmol/l) was seen in 12(18.5%) of 65 children and the remaining 81.5% children had normal serum sodium level (serum sodium 135-145 mmol/l). Among the hyponatremia group all children developed more than one seizure during the same febrile episode. The mean serum sodium level in patients with single and recurrent seizure was 138.48±2.17mmol/l and 135.27±3.11mmol/(P<0.001). The relationship between the probability of a recurrent seizure and serum sodium level is statistically highly significant. Conclusion: Estimation of the seum sodium in children with febrile seizures help in deciding for admission in hospital as well as to predict seizure recurrence within the same febrile episode. TAJ 2019; 32(1): 39-45